Full‐Field Modeling of Heat Transfer in Asteroid Regolith: 2. Effects of Porosity. Issue 6 (18th June 2022) - Ryan, Andrew J.; Pino Muñoz, Daniel; Bernacki, Marc; Delbo, Marco; Sakatani, Naoya; Biele, Jens; Emery, Joshua P.; Rozitis, Benjamin
Abstract: The thermal conductivity of granular planetary regolith is strongly dependent on the porosity, or packing density, of the regolith particles. However, existing models for regolith thermal conductivity predict different dependencies on porosity. Here, we use a full‐field model of planetary regolith to study the relationship between regolith radiative thermal conductivity, porosity, and the particle non‐isothermality. The model approximates regolith as regular and random packings of spherical particles in a 3D finite element mesh framework. Our model results, which are in good agreement with previous numerical and experimental datasets, show that random packings have a consistently higher radiative thermal conductivity than ordered packings. From our random packing results, we present a new empirical model relating regolith thermal conductivity, porosity, temperature, particle size, and the thermal conductivity of individual particles. This model shows that regolith particle size predictions from thermal inertia are largely independent of assumptions of regolith porosity, except for when the non‐isothermality effect is large, as is the case when the regolith is particularly coarse and/or is composed of low thermal conductivity material. Plain Language Summary: The temperature of a planetary surface is strongly controlled by the thermal inertia of the surface materials. Specifically, if the surface is covered in a granular regolith, then the size, thermal conductivity, and packing density of the regolith particles strongly affects the surface thermal inertia, which in turn controls surface temperatures. In this work, we use 3D numerical simulations of heat transfer through beds of spherical particles, representing a planetary regolith, to investigate how thermal conductivity and thermal inertia are controlled by the packing density and thermal conductivity of the spheres. Our results are presented in the form of a new empirical model, which could be used to calculate regolith thermal conductivity from knowledge of particle size, composition, and packing density. The use of this model is demonstrated in the typical reverse fashion, where an observed planetary thermal inertia is converted into a predicted regolith particle size. Our model shows that the predicted particle size is largely independent of regolith particle packing density, in contrast to other common regolith models. Key Points: A 3D finite element model is used to study the effects of regolith porosity and material properties on the radiative thermal conductivity A new, empirical model for regolith radiative thermal conductivity is presented We show that regolith packing density has a minimal effect on predicted regolith particle sizes from thermal inertia on airless bodies